A case of accelerated silicosis. (25th July 2018) - Nakládalová, M; Štěpánek, L; Kolek, V; Žurková, M; Tichý, T
Abstract: Abstract Silicosis, caused by inhaling dust containing free crystalline silica, typically has a chronic course, with the numbers of silicosis patients declining globally. Much rarer are the acute and subacute forms. Presented is a case of severe subacute (accelerated) silicosis. The condition resulted from ~2 years of very intense exposure without appropriate personal protective equipment while sandblasting. The patient's initial symptoms were progressive cough, dyspnoea and weight loss. Given his occupational history, typical clinical manifestations and radiological findings, an initial diagnosis of accelerated silicosis was proposed and histologically confirmed. The patient was a candidate for lung transplantation. The case demonstrates a rare but largely preventable disease with serious health effects and a poor prognosis.